Electroacupuncture for psychogenic erectile dysfunction: A resting-state functional magnetic resonance imaging study exploring the alteration of fractional amplitude of low frequency fluctuation - Yang, Yuqing; Qu, Liu; Mu, Linxuan; Yao, Junpeng; Su, Chengguo; Zheng, Qianhua; Zheng, Huabin; Zhang, Peihai; Li, Ying (Frontiers in Human Neuroscience, 2023)
Background Psychogenic erectile dysfunction(PED) can seriously affect emotional and marital wellbeing. Electroacupuncture(EA) is an effective method for treating PED. However, the central mechanisms underlying PED and the beneficial effects of EA treatment are unclear. The purpose of this study was to explore the central mechanisms of PED and to examine the impact of EA on erectile function. Methods: We recruited 14 PED patients and 14 matched normal controls(NCs). PED patients underwent twice rs-fMRI scans, respectively pre- and post-treatment. The NCs only completed one rs-fMRI scan. We used the fractional amplitude of low frequency fluctuation(fALFF) to compare spontaneous neural activity between the PED patients and NCs, and to examine the differences between the pre- and post-EA treatment scans in the PED patients. Results: Scores on the IIEF5, QEQ, and SEAR improved after EA treatment. Compared with the NCs, PED patients showed increased fALFF in the right posterior cingulate cortex(PCC), right dorsolateral prefrontal cortex(DLPFC), right supplementary motor area(SMA), and left middle occipital gyrus. Most of these regions are closely implicated in sexual inhibition. The results of the correlation analysis results indicated that the fALFF of the right PCC was negatively correlated with IIEF5 scores. After treatment, fALFF values were substantially lower in the left triangular part of the inferior frontal gyrus, right DLPFC, right SMA, bilateral PCC and the orbital part of the middle frontal gyrus, and higher in the left middle temporal gyrus and left caudate nucleus. These regions mainly belong to the default mode network(DMN), executive control network(ECN) and primary sensory motor network(SMN). The results of the correlation analysis indicated a positive association between the changes in IIEF5 score and changes in the fALFF value in the right PCC after EA treatment. Conclusion: In conclusion, our study highlights that PED patients have abnormal patterns of activity in the right PCC, right DLPFC, and right SMA mainly involved in the DMN, ECN, and SMN, which could lead to a higher levels of sexual inhibition. EA might regulate the process of sexual inhibition to improve erection function in PED patients probably by modulating spontaneous brain activity in the DMN, ECN, and SMN.